Tadbir as Marine Diplomacy: Ottoman Foreign Jurisdiction in Practice and the Debate of Piracy in Case of Tripoli between 1790s-1835 - Duymus, Kerem (Sebha University, 2024)
The marine diplomacy of Tripoli in the Qaramanlı era was deeply shaped by the Ottoman Foreign Jurisdiction. Yet, especially Yusuf Paşa with his tadbir (Ar.) [governing through taking measures] application carried the implication of this jurisdiction to a global tributary system that all European states as well as USA obeyed. The ignorance of the historians from Europe and USA about the Ottoman Foreign jurisdiction led them to believe that the tributary system of Tripoli was “piracy”. A thorough examination shows that actually even some European and USA consuls in the 19th century were aware of the fact that the tributary system had nothing to do with piracy, but they named this system in this way to express their dissatisfaction. In reality, Yusuf Paşa of Tripoli was successfully applying Ottoman Foreign jurisdiction in form of tributary system. Furthermore, between 1790s and 1835, he was so successful on this application that this system became a global politic in the Mediterranean without using any brute force.
التدبيركدبلوماسية بحرية: الوالية الخارجية العثمانية في املمارسة في حالة طرابلس قبل عام